Imagens de si: das (foto)narrativas de vida à constituição profissional de professores alfabetizadoras - Monteiro, Waldirene Malagrine (2015)
In the current research we analyze the personal and professional Constitution of literacy teachers, facing the relational hues during the course of life. In this sense, the research constitute of theoretical-methodological reflections, that seek to understand the professional constitution as subject-author in dialogue with two public school teachers from the city of Sorocaba, participating in the Research of Educational Practices in Mathematics Study Group, UFSCar- Sorocaba Campus, when considering a conflict and pleading educational space, centered on the problematization of teacher education. Stands, therefore, as a guiding question of this study, how does a teacher constitutes and develops professionally, the experiences of family relationship, initial schooling experiences, and relationships with teachers, people and spaces that were part of their lives in the formation process, especially the choice of teaching. This way, we tried to investigate the nature of the teaching profession, their knowledge, complexities that leverage discoveries about the subjectivities, experiences and professional trajectories, in a continuous and growing process of understanding the educational practice. Thus, the present research, committed to educational reality, particularly in the life stories of a Literacy Teacher, occurred by the information production of the (auto)Biographical narratives and Photo biographical, concerning the Constitution of personal and professional speakers from the research. In the process of data analysis, we organize the following theoretical contribution: Nóvoa (2010); Josso (2005); Souza (2013); Delory-Momberger (2006); Tardif (2003); among other authors that, on a qualitative approach, consider as granted the respect to the constituent elements of training and professional teaching, to seek alternatives for insertion of the teacher in the study center, in front of their singularities, subjectivities and the intensification of senses and meanings of experiences as results we present the fact that the Constitution of a tutor teaching establishes itself in the multi-referentiality, people, places and times, which cross the life and formation stories.